What types of organizations benefit from teams, and how do they benefit? - Jed Devaro; Fidan Ana Kurtulus (University of Massachusetts, Department of Economics, 2011)
Using data from a large cross-section of British establishments, we ask how different firm characteristics are associated with the predicted benefits to organizational performance from using team production. To compute the predicted benefits from using team production, we estimate structural models for financial performance, labor productivity, and product quality, treating the firm's choices of whether or not to use teams and whether or not to grant teams autonomy as endogenous. One of the main results is that many firm characteristics are associated with larger predicted benefits from teams to labor productivity and product quality but smaller predicted benefits to financial performance. For example, this is true for union recognition as measured by the number of recognized unions in an establishment. Similarly, when a particular firm characteristic is associated with lower benefits from teams to labor productivity or product quality, the same characteristic is frequently associated with higher predicted benefits to financial performance. This is true for the degree of financial participation and employee ownership and also for establishment size and a number of industries. These results highlight the advantages of analyzing broader measures of organizational performance that are more inclusive of the wide spectrum of benefits and costs associated with teams than the labor productivity measures frequently studied in the teams literature.
Keywords: 330